2009
DOI: 10.1074/jbc.m807821200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Studies of TIGAR (TP53-induced Glycolysis and Apoptosis Regulator)

Abstract: Activation of the p53 tumor suppressor by cellular stress leads to variable responses ranging from growth inhibition to apoptosis. TIGAR is a novel p53-inducible gene that inhibits glycolysis by reducing cellular levels of fructose-2,6-bisphosphate, an activator of glycolysis and inhibitor of gluconeogenesis. Here we describe structural and biochemical studies of TIGAR from Danio rerio. The overall structure forms a histidine phosphatase fold with a phosphate molecule coordinated to the catalytic histidine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 38 publications
7
96
1
Order By: Relevance
“…In addition to the established role of p53 in cell cycle arrest and apoptosis, recent evidence has demonstrated that p53 reduces glycolytic flux and increases oxidative phosphorylation, halting the Warburg effect. [137][138][139][140][141][142][143] TIGAR (Tp53-induced glycolysis and apoptosis regulator) was identified to function as a fructose-2,6-bisphosphatase (Fru-2,6-BP), antagonizing the third step of glycolysis and thereby redirecting metabolite flux to the pentose phosphate pathway. [138][139][140] Interestingly, basal or low levels of p53 expression have been suggested to provide antioxidant effects and thus elicit cellular protection rather than cell death.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the established role of p53 in cell cycle arrest and apoptosis, recent evidence has demonstrated that p53 reduces glycolytic flux and increases oxidative phosphorylation, halting the Warburg effect. [137][138][139][140][141][142][143] TIGAR (Tp53-induced glycolysis and apoptosis regulator) was identified to function as a fructose-2,6-bisphosphatase (Fru-2,6-BP), antagonizing the third step of glycolysis and thereby redirecting metabolite flux to the pentose phosphate pathway. [138][139][140] Interestingly, basal or low levels of p53 expression have been suggested to provide antioxidant effects and thus elicit cellular protection rather than cell death.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
“…[137][138][139][140][141][142][143] TIGAR (Tp53-induced glycolysis and apoptosis regulator) was identified to function as a fructose-2,6-bisphosphatase (Fru-2,6-BP), antagonizing the third step of glycolysis and thereby redirecting metabolite flux to the pentose phosphate pathway. [138][139][140] Interestingly, basal or low levels of p53 expression have been suggested to provide antioxidant effects and thus elicit cellular protection rather than cell death. [138][139][140] A recent study has discovered an unexpected mechanism of TIGAR to decrease ROS generation at mitochondria.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
See 1 more Smart Citation
“…While this work was in progress, two other crystal structures of Eco-ZnuA were reported [13,14] and are virtually identical in fold to the structure of ZnZnuA form I (Fig. 1).…”
Section: Overall Structure Of Eco-znuamentioning
confidence: 99%
“…6803 MntC (Syn-MntC) [12], and Eco-ZnuA [13,14] as well as the metal-free (apo) structures of Tpa-TroA [15] and mutant Syn-ZnuA (without the His-rich loop) [8] have been determined by X-ray crystallography. The overall architecture of these MBRs is similar to that of other PLBPs from ABC transporter systems.…”
Section: Introductionmentioning
confidence: 99%